Asymmetric one-pot sequential Friedel–Crafts-type alkylation and α-oxyamination catalyzed by a peptide and an enzyme - Akagawa, Kengo; Umezawa, Ryota; Kudo, Kazuaki (Beilstein Journal of Organic Chemistry, 2012)
In the presence of a peptide catalyst and the oxidative enzyme laccase, a one-pot sequential reaction including a Friedel–Crafts-type alkylation of α,β-unsaturated aldehydes followed by an α-oxyamination was realized. The reaction in aqueous solvent to promote the enzymatic oxidation, and the use of a peptide catalyst compatible with such conditions, were essential. The present sequential reaction afforded oxygen-functionalized indole or pyrrole derivatives in a highly enantioselective manner.
Keywords: Friedel–Crafts-type alkylation; laccase; one-pot reaction; organocatalysis; α-oxyamination; resin-supported peptide catalyst

(untitled) - Somei, M.; Yamada, F. (Nat. Prod. Rep., 2004)

(untitled) - Ruiz-Sanchis, P.; Savina, S. A.; Albericio, F.; Álvarez, M. (Chem.–Eur. J., 2011)

(untitled) - Saxton, J. E. (Nat. Prod. Rep., 1997)

(untitled) - Jørgensen, K. A. (Synthesis, 2003)

(untitled) - Bandini, M.; Melloni, A.; Umani-Ronchi, A. (Angew. Chem., Int. Ed., 2004)

(untitled) - Bandini, M.; Melloni, A.; Tommasi, S.; Umani-Ronchi, A. (Synlett, 2005)

(untitled) - Bandini, M.; Eichholzer, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - You, S.-L.; Cai, Q.; Zeng, M. (Chem. Soc. Rev., 2009)

(untitled) - Bartoli, G.; Bencivenni, G.; Dalpozzo, R. (Chem. Soc. Rev., 2010)

(untitled) - Terrasson, V.; de Figueiredo, R. M.; Campagne, J. M. (Eur. J. Org. Chem., 2010)

(untitled) - Zeng, M.; You, S.-L. (Synlett, 2010)

(untitled) - Enders, D.; Grondal, C.; Hüttl, M. R. M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Walji, A. M.; MacMillan, D. W. C. (Synlett, 2007)

(untitled) - Yu, X.; Wang, W. (Org. Biomol. Chem., 2008)

(untitled) - Grondal, C.; Jeanty, M.; Enders, D. (Nat. Chem., 2010)

(untitled) - Ramachary, D. B.; Jain, S. (Org. Biomol. Chem., 2011)

(untitled) - Huang, Y.; Walji, A. M.; Larsen, C. H.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2005)

(untitled) - Enders, D.; Narine, A. A.; Toulgoat, F.; Bisschops, T. (Angew. Chem., Int. Ed., 2008)

(untitled) - Chi, Y.; Scroggins, T.; Fréchet, J. M. J. (J. Am. Chem. Soc., 2008)

(untitled) - Simmons, B.; Walji, A. M.; MacMillan, D. W. C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Routien, J. B. (J. Bacteriol., 1966)

(untitled) - Werner, R. G.; Thorpe, L. F.; Reuter, W.; Nierhaus, K. H. (Eur. J. Biochem., 1976)

(untitled) - Tabata, N.; Tomoda, H.; Takahashi, Y.; Haneda, K.; Iwai, Y.; Woodruff, H. B.; Ōmura, S. (J. Antibiot., 1993)

(untitled) - Brown, S. P.; Brochu, M. P.; Sinz, C. J.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2003)

(untitled) - Zhong, G. (Angew. Chem., Int. Ed., 2003)

(untitled) - Hayashi, Y.; Yamaguchi, J.; Hibino, K.; Shoji, M. (Tetrahedron Lett., 2003)

(untitled) - Sibi, M. P.; Hasegawa, M. (J. Am. Chem. Soc., 2007)

(untitled) - Kano, T.; Mii, H.; Maruoka, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - Simonovich, S. P.; Van Humbeck, J. F.; MacMillan, D. W. C. (Chem. Sci., 2012)

(untitled) - Akagawa, K.; Akabane, H.; Sakamoto, S.; Kudo, K. (Org. Lett., 2008)

(untitled) - Akagawa, K.; Akabane, H.; Sakamoto, S.; Kudo, K. (Tetrahedron: Asymmetry, 2009)

(untitled) - Akagawa, K.; Yamashita, T.; Sakamoto, S.; Kudo, K. (Tetrahedron Lett., 2009)

(untitled) - Akagawa, K.; Fujiwara, T.; Sakamoto, S.; Kudo, K. (Org. Lett., 2010)

(untitled) - Akagawa, K.; Fujiwara, T.; Sakamoto, S.; Kudo, K. (Chem. Commun., 2010)

(untitled) - Akagawa, K.; Kudo, K. (Adv. Synth. Catal., 2011)

(untitled) - Akagawa, K.; Kudo, K. (Org. Lett., 2011)

(untitled) - Akagawa, K.; Suzuki, R.; Kudo, K. (Adv. Synth. Catal., 2012)

(untitled) - Witayakran, S.; Ragauskas, A. J. (Adv. Synth. Catal., 2009)

(untitled) - Kolundzic, F.; Noshi, M. N.; Tjandra, M.; Movassaghi, M.; Miller, S. J. (J. Am. Chem. Soc., 2011)

(untitled) - Ganachaud, C.; Garfagnoli, V.; Tron, T.; Iacazio, G. (Tetrahedron Lett., 2008)

(untitled) - Appayee, C.; Brenner-Moyer, S. E. (Org. Lett., 2010)